A ESCOLA E O INÉDITO VIÁVEL: FUNDAMENTOS IDEOLÓGICOS PARA UMA NOVA HEGEMONIA - FASANO, EDSON (2016)
The theme of this research, of qualitative nature, focuses on educational policy, in a special way, on the relevance of the development of an ideology to be unchained of a specific curriculum, geared to public and popular education. The school curriculum of the middleclass school is marked by hegemonic ideology, that tries to hide the class struggle under the aegis of scientific neutrality. Thus, this research puts itself in opposition to the movement called "Escola sem Partido". The question that guides this research refers to the recognition of the existence of the working classes own ideology and tries to understand their aspects and features, as well as the legitimation of such ideology through the counter-hegemonic curriculum to be implemented in public and popular schools. The study assumes that there is a popular ideology built on the everyday experiences of exploitation and oppression of the lower classes, revolts generators. However, when establishing the common sense, that ideology, in itself, is not able to generate a class consciousness. For this reason, it is emphasized the importance of its questioning in the popular and public school curriculum. In this context, the central objective of this research is to contribute to the development of a transformative curriculum. Considering the above, it was tried to conduct a literature review from the theoretical contributions of Antonio Gramsci and Paulo Freire, on the themes popular ideology and school curriculum, using as a basis for this debate the ideas of the French Marxist Alain Badiou. The research counted, too, with a field research in which there have been four semi-open interviews with renowned Brazilian intellectuals: Gaudêncio Frigotto, José Eustáquio Romão, Luiz Antonio Cunha and Claudio de Oliveira Ribeiro. The study made it possible to confirm the hypothesis presented here and infer, therefore, that a public and popular school can not be made possible following the same curriculum and values of middleclass school